MEDICALLY UNEXPLAINED NEUROLOGICAL SYMPTOMS ON AN ACUTE NEUROLOGY WARD: HEALTHCARE RESOURCE UTILISATION. Issue 11 (9th October 2013) - Gallagher, Paul; Meldrum, Steven; Copstick, Susan; Burnel, Adam; Matthews, Audrey; Brown, Melanie; Walker, Susan; Shah, Pushkar; Razvi, Saif
Abstract : Introduction: Medically Unexplained Neurological Symptoms (MUNS) are the second most common diagnosis in neurology outpatient clinics, accounting for up to 16% of all referrals. 1 Patients with MUNS are frequently admitted for inpatient investigation and management. We reviewed healthcare resource utilisation of patients with MUNS on an acute neurology ward in a tertiary neuroscience centre. Methods: A prospective audit of patients admitted to a 19–bedded acute neurology ward, serving a population of approximately 2.2 million people, was performed. We included those with a clinical diagnosis of MUNS and no associated relevant pathology. Patients with MUNS and co–morbid neurological illness (e.g. epilepsy with non–epileptic attack disorder) or individuals assessed electively on the 20–bedded programmed investigation unit (e.g. for video telemetry) were excluded. Clinical and demographic data were collected using paper and electronic records and the national radiology database. Data were collected with respect to healthcare resource utilisation during the single inpatient stay. This included the duration of admission, neuroimaging, electroencephalography (EEG), electromyography (EMG) performed and time with physiotherapists. Results: Fourteen patients (11 female, median age 39 years, range 19–56) were admitted to the acute neurology ward over a 9–month period (1st April to 31st December 2012). Eleven out of fourteen (78.6%) were transferred from other hospitals and 3 were admitted form home. Median duration in hospital prior to transfer was 5 days (range 0–15, total 51 hospital days). Patients were taking a mean of 5.4 medications (SD 3.9). Three (21.4%) had prior contact with mental health services and 1 had learning difficulties. Previous attendance at an emergency department had occurred in 6/14 (42.9%) patients (total 84 attendances; range 2–31). Nine patients (64.3%) had prior hospital admissions (total 49 admissions; mean 3.5 [SD 5.6]). A functional motor disorder was diagnosed in 9/14 (64.2%); 3/14 (21.4%) had non–epileptic attack disorder (NEAD), 1/14 (7.1%) had both a functional motor disorder and NEAD and 1 had purely sensory symptoms. Median duration of admission was 8.5 days (range 3–64 days, IQR 5.5–15). Over the 9–month period, patients with MUNS accounted for 231 bed–days, equating to 4.4% of the acute neurology ward bed capacity over this period. CT scans were performed in 9/14 (64.3%, total 12 scans); 10/14 (71.4%) had an MRI (total 22 scans, 1.6 per patient). Four (28.6%) had EEG and 4/14 also had EMG (total 7 EMGs). All 11 with functional motor and sensory MUNS had physiotherapy sessions, accounting for 118 sessions (median 5.5 sessions per patient) with 0.5–52.75 hours required for individual patients (median 3.75 hours). Conclusion: Patients with MUNS accounted for 4.4% of the bed occupancy on an acute neurology ward in a tertiary neuroscience centre, with substantial healthcare resource utilisation. This study likely underestimates the overall burden of functional symptoms on the acute neurology ward as only purely functional symptoms were included. A multi–disciplinary approach is required for management of patients with MUNS and needs further study.